Microbiological water quality and sources of contamination along the coast of the Department of Atlántico (Caribbean Sea of Colombia). Preliminary results (2019)
Microbiological sea water quality is a public health problem that has serious repercussions in the tourism and economy of Colombia. This study determines the concentrations of Escherichia coli, Enterococcus faecalis and Clostridium perfringens at eleven beach water points and seven streams along the coast of the Department of Atlántico, Colombia. In seawater, total E. coli, E. faecalis and C. perfringens concentrations were found between 16 and 572 cfu/100 mL, 7–450 cfu/100 ml and 2–125 cfu/100 ml, respectively. The highest counts were observed mainly on urbanised beaches and in correspondence with streams whose waters had a high concentration of faecal origin microorganisms, which represent a serious health risk factor for bathers. Relevant efforts have to be addressed to improve the microbiological quality of these beaches by the establishment of efficient wastewater management programs aimed at enhancing the efficiency of the local treatment plant and the control of illegal sewage pouring onto the coast.